ANTIBIOTIC SUSCEPTIBILITY OF BACTERIAL STRAINS, WITH SPECIAL REFERENCE TO ESCHERICHIA COLI ISOLATED FROM URINARY TRACT INFECTIONS IN RURAL MAHARASHTRA - Salunke, Gaurav V; Gidamudi, Sunil s (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study was to find out the etiology of urinary tract infections (UTIs) in patients attending B.K.L. Walawalkar Hospital, Dervan and to determine their antibiotic sensitivity pattern to currently used antimicrobial agents. Methods: Â A Â cross-sectional Â study Â was Â conducted Â in Â a Â rural Â hospital Â of Â Konkan Â Maharashtra, Â and Â urine Â samples Â were Â collected Â from368 clinically - suspected cases of UTIs using the mid-stream clean catchâ€ method and was tested and cultured using standard procedures. Antimicrobial susceptibility test (AST) was performed for the isolated pathogens according to the Clinical and Laboratory Standards Institute guidelines. Results: Escherichia coli (54.84%) was the most prevalent uropathogen. 76.47% of the isolated E. coli were found to be extended spectrum beta lactamase producers. A higher prevalence rate of resistance was seen among E. coli to the commonly prescribed antibiotic agents. 32 (94.11%) of34 E. coli isolates recovered had multiple antibiotic resistance (MAR), with 16 isolates (50%) possessing MAR indices of 0.6. Conclusion: The study indicates the isolated microorganisms in UTI showed very high resistance to the commonly prescribed antimicrobial drugs. This suggests the monitoring and rational use of the antimicrobial agents. Keywords: Mid-stream, Culture, Uropathogen, Resistance, Multiple antibiotic resistance.